Evaluate
5 0 0 2 + 2 × 5 0 0 + 4 5 0 0 3 − 8 .
Details and assumptions
This problem was originally posed by Gabriel M .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
u clear my dout sir thanxx
wowwww!!
woow talaga
Let a = 5 0 0 , b = 2 . Then, we must find a 2 + a b + b 2 a 3 − b 3 However, we know the difference of cubes factorization , which says that ( a − b ) ( a 2 + a b + b 2 ) = a 3 − b 3 Therefore, the answer is a − b = 5 0 0 − 2 = 4 9 8 .
Thank you Dan.
Quick unrelated note: There's also the "Difference of three cubes" factorization which is a 3 + b 3 + c 3 − 3 a b c = ( a + b + c ) ( a 2 + b 2 + c 2 − a b − b c − c a ) = 2 1 ( a + b + c ) ( ( a − b ) 2 + ( b − c ) 2 + ( c − a ) 2 ) . Note how this also proves the 3-variable AM-GM.
Note that
5 0 0 3 − 8
= 5 0 0 3 − 2 3
= ( 5 0 0 − 2 ) ( 5 0 0 2 + 2 × 5 0 0 + 2 2 )
= ( 5 0 0 − 2 ) ( 5 0 0 2 + 2 × 5 0 0 + 4 )
Hence,
5 0 0 2 + 2 × 5 0 0 + 4 5 0 0 3 − 8
= 5 0 0 2 + 2 × 5 0 0 + 4 ( 5 0 0 − 2 ) ( 5 0 0 2 + 2 × 5 0 0 + 4 )
= 5 0 0 − 2
= 4 9 8
(500^3-2^3)/(500^2+2 500+2^2)=(500-2)(500^2+2 500+2^2)/ (500^2+2*500+2^2)=500-2=498 here we use the identity (a^3-b^3)=(a-b)(a^2+ab+b^2)
500^3 - 8=124999992 500^2+2*500+4=251004 124999992/251004=498
i m also do like that
(500^3-8)/500^2+2 500+4), here, (500^3-8) is to be (500^3-2^3) like this so expansion of a^3-b^3 is (a-b)(a^2+ab+b^2) in this way this sum write like this (500-2)(500^2+2 500+4)/(500^2+2*500+4) so cancel remaining (500-2) result is 498
2500 is error 2*500 is correct
answer for this problem:
Nu:500cube-8=(500 500 500)-8=125000000-8=124999992
De:500square+2 100+4=(500 500)+1000+4=250000+1004=251004
Nu/De=124999992-251004=498
I could not understand this process
Problem Loading...
Note Loading...
Set Loading...
First, we see that 8 = 2 3 .By factoring 5 0 0 3 − 2 3 , we get ( 5 0 0 − 2 ) ( 5 0 0 2 + 2 ∗ 5 0 0 + 2 2 ) . We notice that ( 5 0 0 2 + 2 ∗ 5 0 0 + 2 2 ) is the same as the denominator, so we can divide that out leaving us just with 5 0 0 − 2 = 4 9 8